Intention to Stay and Intention to Leave: Are They Two Sides of the Same Coin? A Cross‐sectional Structural Equation Modelling Study among Health and Social Care Workers. Issue 4 (3rd October 2014) - Nancarrow, Susan; Bradbury, Joanne; Pit, Sabrina Winona; Ariss, Steven
Abstract : Intention to Stay and Intention to Leave: Are They Two Sides of the Same Coin? A Cross‐Sectional Structural Equation Modelling Study among Health and Social Care Workers: Susan NANCARROW, et al . School of Health & Human Sciences, Southern Cross University, Australia— Objectives: "Intention to leave" (ITL) has been used interchangeably with the more positive construct "intention to stay" (ITS). The implicit assumption appears to be that both constructs represent different sides of the same coin. This study challenges this assumption. The objectives were (i) to test whether these constructs were similar measures of the same construct, and (ii) to assess the strength of the relationships between ITL and ITS with work‐related outcomes. Methods: The Workforce Dynamics Questionnaire (WDQ) was administered to 298 staff. The WDQ included two items on ITL and was supplemented with three items on ITS. Structural equation modelling (SEM) was used. Results: The response rate was 43%. The correlation between the two constructs was negative and quite high (r=−0.84), indicating potential issues with discriminant validity. However, the constructs behaved differently in relation to job satisfaction and job integration. ITS was a strong predictor (0.95, p <0.001), whereas ITL was not significantly related (0.34, p =0.195) to JS. The direct effects of JI on ITS was 0.30 and on ITL was −0.42. The indirect effects of JI were more contrasting, being 0.56 for ITS and −0.30 for ITL, via job satisfaction. Conclusions: This is the first study amongst British health and social care workers that has demonstrated that ITS and ITL are not measuring the same construct. While there is overlap, care should be taken when using these constructs interchangeably, particularly when measuring these concepts in organizations and when developing retention programs, policies, or activities to modify ITS and ITL.